2018
DOI: 10.29219/fnr.v62.1285
|View full text |Cite
|
Sign up to set email alerts
|

A novel polysaccharide from the Sarcodon aspratus triggers apoptosis in Hela cells via induction of mitochondrial dysfunction

Abstract: BackgroundPolysaccharides extracted from fungus that have been used widely in the food and drugs industries due to biological activities.ObjectiveThe objective of the present study was to investigate the tumor-suppressive activity and mechanism of a novel polysaccharide (SAP) extracted from Sarcodon aspratus.MethodsThe SAP was extracted and purified using Sepharose CL-4B gel from S. aspratus. The cytotoxicity of SAP on cell lines was determined by MTT method. Cellular migration assays were implemented by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The plates with B. cereus and S. typhimurium were incubated at 37°C for 24 h. The suspension in each well was removed and the microtiter wells were washed for four times with PBS to remove non-adherent cells. Biofilms were stained with MTT solution (prepared with the corresponding medium) and incubated in dark for 3 h at 37°C (34,35). Dimethyl sulfoxide (DMSO) was used to rinse after removal of MTT solution.…”
Section: Inhibition Activitymentioning
confidence: 99%
“…The plates with B. cereus and S. typhimurium were incubated at 37°C for 24 h. The suspension in each well was removed and the microtiter wells were washed for four times with PBS to remove non-adherent cells. Biofilms were stained with MTT solution (prepared with the corresponding medium) and incubated in dark for 3 h at 37°C (34,35). Dimethyl sulfoxide (DMSO) was used to rinse after removal of MTT solution.…”
Section: Inhibition Activitymentioning
confidence: 99%
“…In recent years, various therapeutic means have contributed to the treatment and prevention of cancers, but these methods can cause irreversible side effects. Thus, the immediate task of the new drug research is to pursue the natural alternatives with high therapeutic properties and low toxicity (35). Pholidonone is a natural antitumor stilbene derivative isolated from EtOAc extract of P. cantonensis .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a number of components of CHM can inhibit the growth of tumor cells both in vitro and in vivo, such as polysaccharides, flavones, terpenoids, and phenols [ 21 , 22 , 23 , 24 , 25 , 26 ]. The components of polysaccharides, flavones, and triterpenes in AAEE, AAEE-Pe, and AAEE-Ea were quantified.…”
Section: Discussionmentioning
confidence: 99%